Study of thyroid function in patients admitted in intensive care unit - C., Anjani Kumar; Arepalli, Santhosh Kumar; Chintalapudi, Vaishnavi; B., Suresh (International Journal of Research in Medical Sciences, 2022)
Background: The thyroid gland produces two related hormones, tetraiodothyronine (T4) and triiodothyronine (T3) play a critical role in cell differentiation during development and maintain thermogenic and metabolic homeostasis in the adult. Critically ill patients have been defined as those that by dysfunction or failure of one or more organ system depend on survival from advanced instruments monitoring and therapy. The objective was to study the thyroid dysfunction in critically ill patients admitted in intensive care units and its relation to the mortality and severity of disease. Methods: This is a cross sectional study carried out in Dr. Pinnamaneni Siddhartha institute of medical sciences and research foundation, Chinoutpalli, Andhra Pradesh from 1st January 2022 to 30th September 2022 involving 100 patients. Patients of age above 18 years, both sexes, admitted to intensive care units with critical illness were analyzed and approved by institutional ethics committee of Dr. PSIMS and RF data were entered in MS-excel and analyzed in SPSS V22 software. Descriptive statistics, Mann-Whitney U test, logistic regression, ROC curves were applied. P values were reported for all statistical tests and a value of<0.05 was considered to be significant. Results: Out of 100 critically ill patients out of which 17 patients had sepsis, 18 had acute renal failure, 19 patients had acute respiratory failure, 19 patients had diabetic ketoacidosis, 16 patients had congestive cardiac failure, and 11 patients had stroke and their correlation with t3 hormone decrement showed positive correlation. Conclusions: Thyroid profile can be used in predicting the mortality in ICU patients.